A Real-Time Research Platform to Study Vestibular Implants With Gyroscopic Inputs in Vestibular Deficient Subjects - Nguyen, T. A. Khoa; Ranieri, Maurizio; DiGiovanna, Jack; Peter, Otto; Genovese, Vincenzo; Perez Fornos, Angelica; Micera, Silvestro (IEEE transactions on biomedical circuits and systems, 2014)
Researchers have succeeded in partly restoring damaged vestibular functionality in several animal models. Recently, acute interventions have also been demonstrated in human patients. Our previous work on a vestibular implant for humans used predefined stimulation patterns; here we present a research tool that facilitates motion-modulated stimulation. This requires a system that can process gyroscope measurements and send stimulation parameters to a hybrid vestibular-cochlear implant in real-time. To match natural vestibular latencies, the time from sensor input to stimulation output should not exceed 6.5 ms. We describe a system based on National Instrument's CompactRIO platform that can meet this requirement and also offers floating point precision for advanced transfer functions. It is designed for acute clinical interventions, and is sufficiently powerful and flexible to serve as a development platform for evaluating prosthetic control strategies. Amplitude and pulse frequency modulation to predetermined functions or sensor inputs have been validated. The system has been connected to human patients, who each have received a modified MED-EL cochlear implant for vestibular stimulation, and patient tests are ongoing.